Measurements of the stratospheric Density and Temperature Profiles in Hanoi by a Rayleigh Lidar - Tuan, Nguyen Xuan; Trung, Dinh Van; Binh, Nguyen Thanh; Hai, Bui Van (Communications in Physics, 2014)
The molecular density and temperature profiles of the stratosphere in Hanoi are measured by a Rayleigh lidar. The profiles have the spatial resolution of 120 m and the temporal resolution of 1h. Their bottom height and top height are 20 km and 57 km, respectively. The atmospheric molecule density profile is directly derived from the correction-range lidar signal. The temperature profile is deduced from the molecular density profile based on the assumptions of the hydrostatic equilibrium and the ideal-gas law. Lidar measurements show good agreement with the molecular density and the temperature profiles from the MSISE-90 atmospheric model. Maximum errors of the density and temperature are found to be \(± 0.9\)% and \(± 3.4\)~K, respectively.The position and the temperature of the stratopause in Hanoi are determined to be about 49 km and 270 K. Database of lidar in a long time might reveal the characteristic and the structure of the stratosphere in Hanoi, Vietnam.